2009
DOI: 10.1029/2007sw000379
|View full text |Cite
|
Sign up to set email alerts
|

A technique for short‐term warning of solar energetic particle events based on flare location, flare size, and evidence of particle escape

Abstract: We have developed a technique to provide short‐term warnings of solar energetic proton (SEP) events that meet or exceed the Space Weather Prediction Center threshold of J (>10 MeV) = 10 pr cm−2 s−1 sr−1. The method is based on flare location, flare size, and evidence of particle acceleration/escape as parameterized by flare longitude, time‐integrated soft X‐ray intensity, and time‐integrated intensity of type III radio emission at ∼1 MHz, respectively. In this technique, warnings are issued 10 min after the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
162
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(168 citation statements)
references
References 66 publications
(96 reference statements)
3
162
1
2
Order By: Relevance
“…Finally, for intermediate cases, where 1/3 < I 10 /I p < 0.85, the integration ends when the SXR peak flux had dropped by 1/3. This approach differs from the one presented in Laurenza et al (2009) who, instead of the flare start, used as the start time of the integration the 1/3 power point of the rise, under the argument that the SXR maximum is immediately obtained for real-time space weather forecasts and hence, the computed parameters are useful for such purposes. On the other hand, we applied a different criterion since we noticed that in some ''brief-duration'' cases the integration with the use of the 1/3rd criterion stopped at an earlier time that was not representative of the overall radio characteristics of these events.…”
Section: Sfs Datasetmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, for intermediate cases, where 1/3 < I 10 /I p < 0.85, the integration ends when the SXR peak flux had dropped by 1/3. This approach differs from the one presented in Laurenza et al (2009) who, instead of the flare start, used as the start time of the integration the 1/3 power point of the rise, under the argument that the SXR maximum is immediately obtained for real-time space weather forecasts and hence, the computed parameters are useful for such purposes. On the other hand, we applied a different criterion since we noticed that in some ''brief-duration'' cases the integration with the use of the 1/3rd criterion stopped at an earlier time that was not representative of the overall radio characteristics of these events.…”
Section: Sfs Datasetmentioning
confidence: 99%
“…This is evident for forecasting systems of SEP events that rely either on remote-sensing observations of the Sun (Laurenza et al 2009;Núñez 2011;Papaioannou et al 2015) or on in situ measurements (Posner 2007). In particular, the achieved warning time at a subset of common SEP events between the technique furnished by Laurenza et al (2009) and the concept of Posner (2007) has shown that the former leads to a median warning time of 55 min and the latter of 50 min in advance of the National Oceanic and Atmospheric Administration (NOAA) event threshold crossing (10 pfu at >10 MeV).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intensity enhancements of protons in the energy range 54.8-80.3 MeV (average energy 67.7 MeV) were searched for. 7 The energy channel was purposely chosen well above the typically-used >10 MeV proton channel (e.g., Laurenza et al 2009) available from GOES satellites. This was considered appropriate for the goals of the SEPServer project from the point of view of space-weather relevance, as discussed in the Introduction.…”
Section: Event Selectionmentioning
confidence: 99%